Losses and chemical composition of the silts of piatã grass with inclusion of bean residue (Research, Society and Development, 2020)
The objective of this study was to evaluate the gas and effluent losses and the chemical composition of Brachiaria brizantha cv. Piatã with inclusion of bean residue. The inclusion of 0, 10, 20 and 30% of bean residue in Brachiaria grass silage were evaluated in a completely randomized design with five replicates. The results were submitted to analysis of variance and regression, tested by the Tukey test at 5% probability. An increase (P